A cross-sectional study on depression from rural India - Safwi, Sadia R.; Amir, Ali; Khalique, Najam; Gaur, Rakesh K. (International Journal Of Community Medicine And Public Health, 2016)
Background: Depression has been recorded since antiquity. It is an illness that affects both the mind and the body and is a leading cause of disability, workplace absenteeism, decreased productivity and high suicide rates. The present study was conducted in the rural field practice areas of Department of Community Medicine, Jawaharlal Nehru Medical College, Aligarh, Uttar Pradesh. The purpose of this study was to determine the prevalence and severity of depression in the study population and to assess the knowledge regarding causes of depression. Methods: 360 adult respondents were chosen using systematic random sampling to participate in the study. Face to face interviews were then conducted using a semi-structured proforma for collecting the data for socio-demographic and other factors. Depression in the subjects was assessed using the structured and pre-validated Patient Health Questionnaire-9 (PHQ-9). Results: The overall prevalence of depression was 11.9%. Majority of the subjects had moderate grades of depression. But knowledge regarding the causes of depression still comprised of certain supernatural causes. Conclusions: Rates of depression were quite comparable with the other studies. Depression was twice more in females. Apart from increasing mental health services and integrating this with general health services in our community there is also a dire need to focus on greater Information, Education and Communication activities regarding awareness of causes of depression and its prevention.